Investigation of the combination of fractional condensation and water extraction for improving the storage stability of pyrolysis bio-oil. (15th April 2022) - Xu, J.; Brodu, N.; Abdelouahed, L.; Taouk, B.
Highlights: The stability of high temperature fractional condensation bio-oil was improved. The water extraction improved the stability of the water-insoluble fractions. The hydrolysis of sugars can produce interesting chemicals (HMF, furfural, GVL…) Abstract: To improve the storage stability of bio-oils obtained from beech wood intermediate pyrolysis in a drop tube reactor, the combination of three-stage condensation with an additional water extraction system was accomplished to produce separated and purified bio-oil products. The physicochemical properties and composition variation of bio-oil during aging at different storage temperatures (4 °C, room temperature-18 °C, and 50 °C) and different storage times (1, 2, 3, and 4 weeks) were studied and compared to that of fresh bio-oil. The water content of each bio-oil product increased compared to the fresh oil, whereas the pH value decreased slightly. GC chromatography and FT-IR analysis results showed that the chemical composition of the bio-oil changed. All the variations indicate that some reactions, such as polymerization, oxidation, polycondensation, hydrolysis of sugars, and esterification, occurred in the bio-oil samples during storage. Bio-oil products stored at 4 °C and room temperature for 4 weeks had relatively high stability, whereas the accelerated aging of bio-oil stored at 50 °C revealed a significant change in its chemical composition. The additional water extraction step specifically improved the stability of the water-insoluble fractions of the bio-oil products. However, the water-soluble fractions were not as stable as the fractions before water extraction. The high content of acid in the water-soluble fractions made it an appropriate medium for hydrolysis sugar and to produce interesting chemical components, 5-(Hydroxymethyl) furfural (HMF), 2(5H)-furanone, furfural, furan, 2, 5-dimethyl- and γ-Valerolactone (GVL).